Analisis Pengaruh Permintaan Ayam Pedaging terhadap Pendapatan Pedagang Pengecer di Kabupaten Tolitoli - Supamri, Supamri; Haryono, Indah Widyastuti (Fakultas Peternakan Universitas Madako Tolitoli, 2024)
Broiler chicken is one of the most important poultry commodities in meeting the protein needs of Indonesian society. Demand for broiler meat in traditional markets is influenced by various social, demographic, and economic factors, which require further investigation. This study aims to analyze the effect of age, gender, education, family dependents, income, and broiler chicken prices on demand in Susumbolan Market and Bumi Harapan Market, Tolitoli Regency. The research employed a survey method involving 30 broiler meat traders selected through purposive sampling. Data were collected through interviews using a structured questionnaire and analyzed using multiple linear regression to determine the effect of each variable on broiler chicken demand. The results revealed that income and price variables had a significant effect on demand, while age, gender, education, and family dependents showed no significant influence. Simultaneously, all independent variables affected the demand for broiler meat in both markets. These findings indicate that economic factors are more dominant than demographic factors in determining broiler chicken demand. It can be concluded that higher consumer income increases demand for broiler chicken, while higher prices decrease demand. This study provides valuable insights for traders, farmers, and policymakers in formulating marketing strategies and pricing policies to enhance competitiveness and improve the welfare of livestock sector stakeholders.